The Role of Media Sources for COVID-19 Information on Engaging in Recommended Preventive Behaviors among Medicare Beneficiaries Aged ≥ 65 Years - Ng, Boon Peng (J Gerontol B Psychol Sci Soc Sci, 2021)
OBJECTIVES: The public relies on various media sources and communication platforms for receipt of COVID-19 information. Therefore, identifying the primary sources of COVID-19 information among older adults can be valuable, as it can enable information on life-saving measures to be effectively disseminated to this population. METHODS: We analyzed the Medicare Current Beneficiary Survey COVID-19 Supplement that was administrated from June 2020 through July 2020 (n=8,050). A survey-weighted logistic model was conducted to examine the association between sources of COVID-19 information Medicare beneficiaries most relied on (i.e., traditional news sources, social media, comments/guidance from government officials, other webpages/internet, friends/family members, and health care providers) and engaging in all three recommended preventive behaviors (i.e., mask wearing, social distancing, and handwashing). RESULTS: Among study participants, 89.8% engaged in all three recommended preventive behaviors. Approximately 59.3% of beneficiaries reported that they most relied upon traditional news sources for COVID-19 information; 11.4% reported health care providers; 10.6% reported comments/guidance from government officials; 8.8% reported other webpages/internet, 8.6% reported friends/family members; and 1.3% reported they relied upon social media. Beneficiaries who relied on comments/guidance from government officials for COVID-19 information (vs. traditional news sources) were more likely to engage in preventive behaviors (OR=1.68, 95% CI=1.20,2.35). However, those who relied on COVID-19 information from friends/family members (vs. traditional news sources) were less likely to engage in preventive behaviors (OR=0.56, 95% CI=0.44,0.73). DISCUSSION: Our findings can inform decision making about the effective communication sources to reach Medicare beneficiaries for public health messaging regarding preventive measures, including COVID-19 vaccination.